An Analysis of Code Switching in Students’ Speaking Test as English Foreign Language Learners - Nisa, Khairun; Septiawan, Habi; Deviyanti, Rafista (Universitas Islam Negeri Raden Intan Lampung, 2021)
This research aims at finding out types of code switching occurred in students’speaking test of EFL learner, the percentage of each type, and finding out the students’reasons in switching their language.Threetypes of code switching proposed by Poplack (1980); intra-sentential switching, inter-sentential switching, and tag switching were analyzed in this descriptive qualitative study. There was one class as the sample of this research. After gaining the data, the researcher categorized the data based on three types of code switching mentioned above. The result revealed that all three types of code switching appears in the students’ speaking. The first type, intra - sentential switching, it tends to be the main type of switching (69.49%), followed by intra-sentential switching (27.12%). Different from those two types, tag switching seems to occur the least frequent type of switching that appeared in the comments (3.39%). Then, the researcher also classified the data into seven reasons in doing code switching according to Hoffman (1991). There are still some other reasons found by the researcher in conducting the research.